Emerging Nutritional Problem of Adult Population: Overweight/Obesity and Associated Factors in Addis Ababa City Communities, Ethiopia—A Community-Based Cross-Sectional Study - Tsedeke Wolde Hailemariam; Samrawit Solomon Ethiopia; Andamlak Gizaw Alamdo; Haimanot Ewnetu Hailu (Journal of Obesity)
Background. Obesity is an emerging public health problem in developing countries. There is limited study conducted in Ethiopia to determine the prevalence of obesity and its associated factors among adult population. Therefore, this study aimed at determining the prevalence of overweight/obesity and the associated factors among adults aged 25–64 years in Addis Ababa city community residents, Ethiopia. Methods. A community-based cross-sectional study was conducted from April 10, 2017, to May 20, 2017, in Addis Ababa. A total of 512 adults were recruited. A two-stage cluster followed by a systematic random sampling technique was used for sample selection. Data were collected using questionnaires and anthropometric measurements. The adjusted odds ratio (AOR) with a 95% CI was reported to show the strength of association. A P value < 0.05 was considered statistically significant. Results. A total of 484 adults participated in the study with a response rate of 94.5%. The prevalence of overweight and obesity among study participants was found to be 99 (21.5%) and 14 (2.9%), respectively. Males were 90% less likely to be obese when compared to females (AOR = 0.10 (95% CI: 0.01–0.84)). Illiterate people were 94% less likely to be obese compared to those who were literate people (AOR = 0.06 (95% CI: 0.01–0.44)). Nonhypertensive individuals were 86% less likely to be obese when compared to hypertensive (AOR = 0.14 (95% CI: 0.03–0.69)). Conclusion. The combined prevalence of overweight and obesity was found to be considerably high in Addis Ababa city residents compared to the national figure. Being female, literate, and presence of hypertension are independent predictors of overweight/obesity in the study population. Thus, the concerned bodies should initiate efforts to tackle the newly emerging public health problem of the country and promote healthy lifestyle behaviors in the inhabitants of city settings.